Performance of a mixed-use ground source heat pump system in Stockholm - Spitler, Jeffrey D.; Gehlin, Signhild E. A (CLIMA 2022 conference, 2022)
The 6300 m2 two-story Studenthuset building at Stockholm University in Stockholm, completed in 2013, was thoroughly instrumented. Space heating and hot water are provided by a ground source heat pump (GSHP) system consisting of five 40 kW off-the-shelf water-to-water heat pumps connected to 20 boreholes of 200 m depth in hard rock. Space cooling is provided by direct cooling from the boreholes. This system has now been monitored for five years. This paper presents the results in the form of a range of performance indicators that describe the short-term and long-term system performance. Performance factors are computed for several boundaries defined by the IEA HPT Annex 52 boundary schema. Seasonal, monthly, daily, and binned performance factors for both heating and cooling operation are presented and discussed. Contrary to expectations based on thermodynamic theory, the performance is better correlated to the quantity of heating or cooling provided than it is to the exiting fluid temperatures from the ground heat exchanger. Despite being in Stockholm, the building rejects about 30% more than it extracts, leading to a minimal temperature increase over the five measured years. The analysis indicates that if operated as is, the GHE will not exceed its temperature constraints for many decades. The five-year seasonal performance factor (SPF) for combined heating and cooling is 5.2±0.2 considering only the heat pump and source-side circulating pump. However, the load-side distribution system and Legionella protection systems result in a significant decrease in the 5-year combined heating and cooling SPF at the outer boundary to 1.8±0.3.